Analisis Pengaruh Perubahan Beban Terhadap Heat Rate pada Unit Pembangkit Listrik Tenaga Uap (PLTU) Jeneponto 2 135 MW - Nur Hamzah; A.M. Shiddiq Yunus; Dwiki Dirgantama (Politeknik Negeri Ujung Pandang, 2020)
The heat rate is a parameter that can indicate the reliability of the Steam Power Plant and is defined as the amount of heat from the fuel needed to produce 1 kWh of electricity. This study aims to analyze the effect of load changes on heat rate and its optimum value. Heat rates can be expressed in GPHR (Gross Plant Heat Rate) and NPHR (Net Plant Heat Rate). The method used is to identify and collect data for the last three years related to the determination of the heat rate, then perform data processing and analysis. In 2018, the optimum condition for unit 1 was obtained at a load of 125 MW is NPHR 2432.68 kcal/kWh, while Unit 2 at a load of 135 MW is NPHR value of 2489.65 kcal/kWh. In 2019 the optimum value for NPHR units 1 and 2 at a load of 137 MW are NPHR 2517.07 kcal/kWh and NPHR 2527.48 kcal/kWh, respectively. In 2020 the optimal value for Unit 1 is at a load of 135 MW, NPHR 2529.5 kcal/kWh, while Unit 2 is at a load of 137 MW, NPHR 2567.53 kcal/kWh. It can be concluded that an increase in load causes a decrease in the heat rate